2014
DOI: 10.1002/cncr.29203
|View full text |Cite
|
Sign up to set email alerts
|

The importance of disclosure: Lesbian, gay, bisexual, transgender/transsexual, queer/questioning, and intersex individuals and the cancer continuum

Abstract: Precis The Lesbian, Gay, Bisexual, Transgender/Transsexual, Queer/Questioning, Intersex (LGBTQI) population experiences cancer health disparities due to lack of disclosure and knowledge about increased cancer risk. Oncology health care providers and institutions should create environments that encourage disclosure of sexual orientation and identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…First, 61.2% of rural lesbians and 55% of urban lesbians had not been asked about their sexual orientation by their WHCP. These rates are disturbingly high given that knowledge of one's unique sexual identity and behavior on the part of women's healthcare providers is particularly crucial for the provision of appropriate and affirming care [68][69][70] . Given these low rates, it is not surprising that only 21.4% of rural lesbians and 25.4% of urban lesbians indicated that they had been provided with appropriate safe-sex education by their WHCP, with less than 20% of both samples reporting that their last HIV/STI screening was instigated by their provider.…”
mentioning
confidence: 99%
“…First, 61.2% of rural lesbians and 55% of urban lesbians had not been asked about their sexual orientation by their WHCP. These rates are disturbingly high given that knowledge of one's unique sexual identity and behavior on the part of women's healthcare providers is particularly crucial for the provision of appropriate and affirming care [68][69][70] . Given these low rates, it is not surprising that only 21.4% of rural lesbians and 25.4% of urban lesbians indicated that they had been provided with appropriate safe-sex education by their WHCP, with less than 20% of both samples reporting that their last HIV/STI screening was instigated by their provider.…”
mentioning
confidence: 99%
“…[6][7][8] Stigmatizing encounters or fears of expected bias and mistreatment have resulted in a certain unwillingness to disclose sexual orientation in healthcare settings. [9][10][11][12] Non-disclosure for LGB adults may, consequently, have significant health and mental health risks. 6 A study conducted in the United States, for instance, demonstrated that non-disclosure among LGBs with cancer increased distress and negatively affected health outcomes and subsequent referrals to suitable care settings.…”
Section: Disclosure Of Sexual Orientation For Lgb Ayas In Healthcarementioning
confidence: 99%
“…Conversely, when providers reflect upon sexual diversity and LGB specific issues and concerns in their practice, LGB AYAs are often more forthcoming, leading to positive health and mental health outcomes, and promoting health-seeking behaviours. 10 Practices that acknowledge LGB AYAs can increase access to care and foster equitable and informative service provision.…”
Section: Disclosure Of Sexual Orientation For Lgb Ayas In Healthcarementioning
confidence: 99%
“…Although, the abbreviation suggests a homogeneous group, it includes a wide range of people 1 in part because it combines sexual orientation with gender identity. 2 Sexual orientation is the "enduring emotional, romantic, sexual or affectional attraction to another person". 3 For gay men, this attraction is primarily to men, and for lesbians, this attraction is primarily to women.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This makes sexual minorities one of the most understudied and consequently underserved groups in health disparities research. 2 A history of perceived and endured social stigma attached to being a sexual minority ties into a reluctance of some, particularly older adults, to self-identify as LGBT, resulting in their absence from research and its findings.…”
Section: Introductionmentioning
confidence: 99%